Advances in in vivo magnetic resonance spectroscopy for metabolic disorders - Yuliya Kupriyanova; Yuliya Kupriyanova; Vera Schrauwen-Hinderling; Vera Schrauwen-Hinderling; Vera Schrauwen-Hinderling (Frontiers in Endocrinology)
Magnetic Resonance Spectroscopy (MRS) and Magnetic Resonance Imaging (MRI) yield valuable metabolic information in a non-invasive way. The current mini review addresses current practice and recent advances in metabolic research, specifically in the field of obesity, insulin resistance and diabetes. The potential application of MRS to investigate lipid and glycogen stores, as well as energy metabolism are reviewed and novel methods to extract more detailed information on fatty acid composition or newly detectable metabolites such as acetylcarnitine or nicotinamide adenosine dinucleotide (NAD+) and NADH are discussed. These advances are based on optimization of post-processing or on the application of new schemes for spectral editing to suppress unwanted signal. The advantage of MRS is that it gives real-time dynamic information and therefore, metabolism can be investigated during physiological challenges, such as exercise, food intake or immediate drug action. Due to its non-invasive nature, repeated measurements are possible with MRS, to monitor treatments and interventions and also organs that are not easily accessible for biopsies, such as the liver or the heart can be probed by MRS. When investing in further methodological development, new applications will arise, advancing our understanding of metabolic disease and giving us tools to identify successful treatment and prevention strategies in individuals at risk.